A tale of two cities - Dickens, Charles; Ramos, Ma. Renita Diano; Autencio, Gary (Manila : Lampara Publishing House, 2011)
"The year 1775 is an age of many contradictions, an extraordinary period. France is prosperous, unlike England where chaos rules. Cruel acts are performed in the name of Christianity."--Cover.
Keywords: France -- History -- Revolution, 1789-1799 -- Fiction; Historical fiction